Effect of ripeness and viticultural techniques on the rotundone concentration in red wine made from Vitis vinifera L. cv. Duras. (8th August 2014) - Geffroy, O.; Dufourcq, T.; Carcenac, D.; Siebert, T.; Herderich, M.; Serrano, E.
Abstract Background and Aims Rotundone, a potent aroma compound responsible for peppery aroma and flavour in Shiraz, was detected recently in Vitis vinifera L. cv. Duras wines. In 2011 and 2012, two separate experiments were carried out to determine the effect of ripeness and viticultural techniques on rotundone concentration in Duras wine. Methods and Results Rotundone was measured in wines prepared by microvinification techniques (1 L Erlenmeyer). Accumulation of this compound in wines depended on vintage conditions and the degree of ripening, such that a higher concentration of rotundone was reached 44 days after mid‐veraison. Application of exogenous jasmonic acid and grape thinning did not significantly affect rotundone concentration, whereas leaf removal strongly reduced rotundone concentration. Wine from the irrigated treatment had a higher concentration of rotundone, and in most cases, vine water status over the veraison–harvest period was identified as a key variable that was well correlated with observed intraplot variability. Conclusions These findings confirm that some common viticultural practices can be used to manipulate the peppery character in red wine. Significance of the Study Our results may assist grape growers to produce Duras, Shiraz and other cultivars where rotundone makes an important contribution to wine aroma.